Digital spatial profiling identifies phospho-JNK as a biomarker for early risk stratification of aggressive prostate cancer - Eickelschulte, Samaneh; Kaczorowski, Adam; Janke, Florian; Riediger, Anja Lisa; Lazareva, Olga; Böning, Sarah; Kristiansen, Glen; Schwab, Constantin; Stenzinger, Albrecht; Sültmann, Holger; Duensing, Stefan; Duensing, Anette; et al. (Frontiers in oncology, 2025)
BackgroundProstate cancer (PCa) is a highly heterogeneous disease, ranging from indolent to highly aggressive forms. Ongoing research focuses on identifying new biomarkers to improve early risk stratification in PCa, addressing current limitations to accurately evaluate disease progression. A promising new approach to aid PCa risk stratification is digital spatial profiling (DSP) of PCa tissue.MethodsA total of 94 regions of interest from 38 PCa patients at first diagnosis were analyzed for the expression of 44 proteins, including components of the PI3K/AKT, MAPK, and cell death signaling pathways as well as immune cell markers. An additional validation cohort consisting of 154 PCa patients with long-term follow-up data was analyzed using immunohistochemistry (IHC) to assess the consistency of the identified biomarkers across a larger sample set.ResultsDSP identified the proliferation marker Ki-67 and phosphorylated c-Jun N-terminal protein kinase T183/Y185 (p-JNK), a member of the MAPK signaling pathway, as significantly upregulated proteins in aggressive PCa (Gleason grades 4 or 5) compared to indolent disease (Gleason grade 3; p<0.05). The upregulation of p-JNK was confirmed by IHC. High p-JNK expression was associated with a shorter time to biochemical recurrence (log-rank, p=0.1).ConclusionOur results indicate that p-JNK may contribute to PCa progression and serve as an early biomarker for aggressive PCa stratification. Identification of this biomarker through DSP could prove crucial in advancing disease management and addressing the critical unmet need for more targeted therapies in the treatment of PCa. Further studies are warranted to evaluate the role of p-JNK in PCa progression.